Localization induced by pressure in pyrochlore Bi2Ir2O7. Issue 18 (15th December 2017) - Liu, Wei; Han, Hui; Ling, Langsheng; Ma, Long; Pi, Li; Zhang, Lei; Zhang, Yuheng
Abstract: In this work, the resistivity and magnetization of Bi2 Ir2 O7 are investigated under hydrostatic pressure. At ambient pressure, the resistivity of Bi2 Ir2 O7 exhibits a metallic behavior with the decrease of temperature. When the pressure is applied, a metal-insulator phase transition at low temperature is induced under a pressure of ∼ 0.48 GPa. The metal-insulator phase transition temperature ( T MI ) increases linearly with pressure as d T MI / dP = 3.4 ± 0.3 K / GPa . The temperature dependence of resistivity [ ρ ( T ) ] in the pressure-induced insulating phase exhibits a thermal activation behavior ( ρ = ρ 0 e Δ E / k B T ), where the thermal activation energy ( Δ E ) increases monotonously with the pressure. Meanwhile, the magnetization is enhanced by the pressure, which indicates an enhancement of magnetic ordering. The results suggest that localization occurs due to the magnetic ordering induced by the pressure, which confirms the magneto-electronic coupling in Bi2 Ir2 O7